2017
DOI: 10.1534/genetics.116.197376
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ceruloplasmin as a Gene that Affects Susceptibility to Glomerulonephritis Through Macrophage Function

Abstract: Crescentic glomerulonephritis (Crgn) is a complex disorder where macrophage activity and infiltration are significant effector causes. In previous linkage studies using the uniquely susceptible Wistar Kyoto (WKY) rat strain, we have identified multiple crescentic glomerulonephritis QTL (Crgn) and positionally cloned genes underlying Crgn1 and Crgn2, which accounted for 40% of total variance in glomerular inflammation. Here, we have generated a backcross (BC) population (n = 166) where Crgn1 and Crgn2 were gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…Here, we demonstrate that Bcat1 is a druggable target for controlling inflammation in two distinct chronic inflammatory diseases characterized by antibody-mediated end-organ damage with macrophage infiltration. The rat model of crescentic glomerulonephritis in the WKY strain is dependent on macrophage infiltration and activation in response to glomerular deposition of immunoglobulin 21 59 60 . Primary macrophages from the WKY strain show a genetically determined Hif-1α-mediated glycolytic transcriptome signature during their differentiation 61 , suggesting a genetically determined metabolic state that could explain their unique susceptibility to glomerular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate that Bcat1 is a druggable target for controlling inflammation in two distinct chronic inflammatory diseases characterized by antibody-mediated end-organ damage with macrophage infiltration. The rat model of crescentic glomerulonephritis in the WKY strain is dependent on macrophage infiltration and activation in response to glomerular deposition of immunoglobulin 21 59 60 . Primary macrophages from the WKY strain show a genetically determined Hif-1α-mediated glycolytic transcriptome signature during their differentiation 61 , suggesting a genetically determined metabolic state that could explain their unique susceptibility to glomerular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Copper may also have a role in the immune system response to inflammation (67)(68)(69)(70)(71)(72)(73)(74). In inflammatory conditions, subjects exhibited higher mean serum copper concentrations related to disease activity (67,68).…”
Section: Prodrug Of β-D-n4-hydroxycytidine (Eidd-2801mentioning
confidence: 99%
“…In vitro studies have shown that ceruloplasmin may have a pathophysiological role in inflammatory diseases, acting as a physiologic inhibitor of myeloperoxidase (MPO) (72). Another study in a crescentic glomerulonephritis (Crgn) animal model showed the down-regulation of ceruloplasmin by RNA interference (RNAi), decreased markers of glomerular proinflammatory macrophage activation and suppressed a physiological response (73). Exogenous copper decreased the formation of systemic lupus erythematosus (SLE) cells in rats with a hydralazine induced collagen disease (74).…”
Section: Prodrug Of β-D-n4-hydroxycytidine (Eidd-2801mentioning
confidence: 99%
“…12,13 Superoxide anions are the precursor of most other ROS, 35 and their production by macrophages has been shown to be a prominent contributor to the glomerular injury in glomerulonephritis. 15,36,37 To test whether deferiprone protects cells from superoxide induced oxidative stress, we stimulated BMDMs with phorbol 12-myristate 13-acetate (PMA), which is a widely used superoxide inducer in innate immune cells such neutrophils and macrophages. 38,39 Deferiprone markedly decreased the superoxide anions detected in stimulated BMDMs ( Figure 3A).…”
Section: Deferiprone Ameliorates Oxidative Stress By Directly Neutralmentioning
confidence: 99%
“…This latter finding suggested that macrophage iron metabolism could contribute to the pathogenesis of crescentic glomerulonephritis. 15 Iron participates in many aspects of cellular biology and is essential for life as its deprivation leads to inactivation of ribonucleotide reductase (RNR), the enzyme essential for DNA synthesis. [16][17][18] Thus iron chelation emerges as an alternative anti-cancer and immunosuppressive therapy.…”
Section: Introductionmentioning
confidence: 99%